Psychopathic traits moderate relationships between parental warmth and adolescent antisocial and other high-risk behaviors - Chinchilla, Melanie A. (Criminal justice and behavior, 2016)
Risk and protective factors for antisocial behavior may operate differently for youth with versus without psychopathic traits. No prior studies address positive parenting in youth with a clinical measure of psychopathic traits. This study tested whether psychopathic traits reduce responsiveness to parental warmth in terms of conduct problems, substance use, and risky sexual behavior and the alternative perspective that psychopathic traits reduce responsiveness to harsh parenting, but not responsiveness to nurturance among 214 ethnically diverse male and female adolescent detainees. Multiple regression indicated that, for adolescents with low and medium levels of affective traits?but not adolescents with high levels of these traits?higher levels of warmth were associated with marginally fewer conduct disorder symptoms and with lower levels of substance use. Similarly, the association between warmth and substance use was stronger in youth with lower levels than for youth with high levels of overall psychopathy.